Fraud examination - Albrecht, W. Steve; Albrecht, Conan C.; Albrecht, Chad O. (Mason, OH : Thomson Business and Professional Pub., 2006)
This text prepares readers to identify, detect, investigate, and prevent financial fraud. It outlines the nature of fraud and the different types of fraud.
Includes bibliographical references (p. 619-620) and index.
oif 19/08/15
Loans
Keywords: Fraud; Forensic accounting; Fraud investigation